Origineel op Gemeente-archief Den Haag, nr.K 1976-10-03-46. Demonstratie tegen de duurte op 4 juni, Binnenhof
Origineel op Gemeente-archief Den Haag, nr.K 1976-10-03-46. Demonstratie tegen de duurte op 4 juni, Binnenhof.